The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2519/jospt.2010.3264
|View full text |Cite
|
Sign up to set email alerts
|

Patient Education Based on Principles of Cognitive Behavioral Therapy for a Patient With Persistent Low Back Pain: A Case Report

Abstract: feelings, and behaviors. [2][3][4][5]15,16,28,[46][47][48] It also indicates that relationships are dynamic. 3,4,15,16,[46][47][48] Therefore, relationships characterized by problematic behaviors and emotions are modifiable by mitigating dysfunctional thought patterns through directed, systematic, and goal-oriented treatments. 6,15,16 Typically, CBT involves self-reflection of thought processes on the part of a patient that is partially guided by analysis of a patient's thinking by a clinician.This evaluative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…[53][54][55] Cognitive-behavioral training (CBT), although promoted as a potentially useful method for helping patients overcome personal barriers to exercise, has met with limited effectiveness. [55][56][57] According to Rauch et al, "there is no evidence in how physiotherapists manage lack of confidence." 58(p249) In contrast, several studies suggest that self-management approaches targeting self-efficacy show promise for improving exercise adherence.…”
Section: Discussionmentioning
confidence: 98%
“…[53][54][55] Cognitive-behavioral training (CBT), although promoted as a potentially useful method for helping patients overcome personal barriers to exercise, has met with limited effectiveness. [55][56][57] According to Rauch et al, "there is no evidence in how physiotherapists manage lack of confidence." 58(p249) In contrast, several studies suggest that self-management approaches targeting self-efficacy show promise for improving exercise adherence.…”
Section: Discussionmentioning
confidence: 98%
“…255 Henschke et al, 144 in a recent Cochrane Review, concluded there is moderate quality evidence that operant therapy and behavioral therapy are more effective than waiting list or usual care for short term pain relief in patients with chronic low back pain, but no specific type of behavioral therapy is superior than another. In the intermediate to long term, there is no established difference between behavioral therapy and group exercise for management of pain or depressive symptoms in patients with chronic low back pain.…”
Section: Clinical Guidelines: Interventionsmentioning
confidence: 99%
“…17 Alternatively, pain education programs have targeted psychological factors that may be linked to elevated pain processing or a central sensitization response. 48,49,57 Discriminative validity to justify usage of a pain mechanisms-based approach has been demonstrated, 61 but evidence of its effectiveness in physical therapy outcomes is limited. 28 The purpose of this case report was to describe the management of a patient with chronic LBP and multiple health conditions using a pain mechanismsbased approach.…”
Section: T T Discussionmentioning
confidence: 99%
“…60 The patient was again educated on the physiology of a pain flare-up with chronic LBP. 45,57 He was also encouraged to continue exercise within tolerance.…”
Section: Outcomes Omentioning
confidence: 99%
See 1 more Smart Citation